Monotheism and Yahweh's Appropriation of Baal - Anderson, James S. ca. 21. Jh. (The Library of Hebrew Bible / Old Testament Studies, 2015)
Biblical scholarship today is divided between two mutually exclusive concepts for about the emergence of monotheism, an early-monotheistic Yahwism paradigm and a native-pantheon paradigm. The study identifies five main stages on Israel's journey towards monotheism. Rather than deciding whether Yahweh was originally a god of the Baal-type or of the El-type, this work shuns origins and focuses instead on the first period for which there are abundant sources, the Omride era. Non-biblical sources depict a significantly different situation from the Baalism the Elijah cycle ascribes to King Achab